Dowry Giving in the Customary Marriage of Kofalit Village, Salkma District, South Sorong Regency - Harun Salfle; Rajab Lestaluhu; Muharuddin Muharuddin (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Marriage is a significant part of human life that involves various traditions and rituals that are passed down from generation to generation. In Indonesia, the people of Kofalit Village, Salkma District, South Sorong Regency, Papua, have a traditional marriage tradition that is rich in rituals and processions. This research uses a sociological juridical approach to understand more deeply the tradition of marriage and the process of giving dowry in Kofalit Village. This process involves various stages, from matchmaking to the implementation of the marriage ceremony. The payment of dowry, as one of the important aspects of traditional marriage, involves traditional treasures such as timor cloth, bracelets, beads and Portuguese machetes. This tradition demonstrates the customary values upheld by the people of Kofalit Village, marking the seriousness and commitment of the marriage bond. Thus, this research provides an in-depth insight into how customary marriage traditions are practiced and how the process of giving dowry is carried out in the Kofalit community.